Enhancement of Photocatalytic Activity on TiO2-Nitrogen-Doped Carbon Nanotubes Nanocomposites. (28th July 2013) - Wang, Lingling; Shen, Long; Li, Yihuai; Zhu, Luping; Shen, Jiaowen; Wang, Lijun
Abstract : TiO2 -nitrogen-doped carbon nanotubes (TiO2 -CNx) nanocomposites are successfully synthesized via a facile hydrothermal method. The prepared photocatalysts were systematically characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and thermogravimetric and differential scanning calorimetry analyses (TGA-DSC). The results show that the TiO2 nanoparticles with a narrow size of 7 nm are uniformly deposited on CNx. The photocatalytic activity of the nanocomposite was studied using methyl orange (MO) as a model organic pollutant. The experimental results revealed that the strong linkage between the CNx and TiO2 played a significant role in improving photocatalytic activity. However, the mechanical process for CNx and TiO2 mixtures showed lower activity than neat TiO2 . Moreover, TiO2 -CNx nanocomposites exhibit much higher photocatalytic activity than that of neat TiO2 and TiO2 -CNTs nanocomposites. The improved photodegradation performances are attributed to the suppressed recombination of electrons and holes caused by the effective transfer of photogenerated electrons from TiO2 to CNx.